Concentração bancária no Brasil: 2017-2022 - Rocha, Tiago Negreiros do Couto (Brasil, 2025)
Currently, monetary transfer activities through digital transactions are an increasingly common reality among people of various nationalities and social classes. Innovation trends are influenced by several factors, with one of significant importance being related to its industrial sector. The context addressed in this study will focus on concentration indicators and technological trends in the Brazilian banking sector. The analyzed period will cover 2017-2022, encompassing various factors that were crucial for the current development of the Brazilian banking system, such as the digitalization of the banking environment and the COVID-19 pandemic. This study focuses its efforts on perspectives within the fields of Industrial Economics and Innovation, aiming to understand the relationship between banks, technology, and the acceleration of trends during the observed period. It analyzes the structure of the sector in which Brazilian banks operate, their advantages and strengths within this structure, and how technology has diffused in this sector.